PENGARUH KUALITAS PELAYANAN, PROMOSI, HARGA, KUALITAS PRODUK DAN CITA RASA TERHADAP KEPUASAN PELANGGAN PADA AYAM GEPREK WARUNG ENDUS SIBUAYA - Husna, Arinal (Universitas Labuhanbatu, 2021)
This research aims to know the influence of service quality, promotion, price, product quality and taste of customer satisfaction on the chicken geprek stalls around sibuaya. The population in this study is consumers who buy direct at ayam geprek stalls around sibuaya. In this study, using a sample of 84 people. This study uses simple random sampling method that is where the penarika randomly as to give equal opportunity for every member of the population to express their opinions. In testing the simultaneous (Test F) be aware of the quality of service, promotion, price, product quality and flavour of a positive and significant effect on customer satisfaction. In persial (t Test) note that the known quality of service and the promotion of positive and significant effect on customer satisfaction, while the price, the quality of the product and the taste is not positive and significant effect on customer satisfaction. While targetting and positioning the market is not positive and significant effect on competitive advantage. Through testing Koefisifien the determinant obtained the value of Adjusted R Square of 0,229 or 22.9% customer satisfaction can be explained by the quality of service, promotion, price, product quality and taste while the side 77,1 can be explained by other variables that are not discussed in this study. Testing the feasibility of the research instrument as well as the analysis of the descriptive characteristics of the respondents using SPSS software (Statistical Package For The Social Science).